In Situ and Operando Characterizations of 2D Materials in Electrochemical Energy Storage Devices. Issue 4 (15th April 2021) - Meng, Caixia; Das, Pratteek; Shi, Xiaoyu; Fu, Qiang; Müllen, Klaus; Wu, Zhong-Shuai
Abstract : In‐Situ/Operando Characterization of 2D Materials The recent advances of in‐situ and operando characterization of 2D materials for electrochemical energy storage devices are reviewed in the article number 2000076 by Qiang Fu, Klaus Müllen, Zhong‐Shuai Wu, and co‐workers to comprehensively understand the charge storage and degradation mechanisms. Preparation of 2D materials and the impact of preparation methods on the resulting electrode structure and electrochemical performance, and the mechanisms underlying the operation of supercapacitors and lithium batteries are discussed.